Nearshore business model: Exploring the benefits, risks, challenges, and success factors from multiple case studies - Guedes, J.; Pereira, L. (International Journal of Innovation and Sustainable Development, 2024)
Advanced delivery models enabled by nearshoring models are a common practice by several players in the information technology space, being seen by many as a key differentiator of their offerings and ways of working. Although academics share some enthusiasm for this phenomenon, there are still several gaps in the literature regarding nearshoring, especially on its advantages and disadvantages when compared to offshoring. This research has as its main objectives to provide further visibility into the main benefits, risks, success factors, and challenges of nearshoring by analysing a total of 13 case studies, each with three different sources of evidence that were scrutinised and discussed. The findings suggest that nearshoring can deliver similar benefits as offshoring while considerably reducing risks without detriment in quality. Additionally, it suggests that several common challenges to management usually found in offshoring activities can be avoided, especially by following a set of best practices and success factors.